Analaisis Pelaksanaan Program Peningkatan Mutu Pendidik Di Sekolah Dasar Islam Terpadu Al-Fikri Islamic Green School Pekanbaru - Rizal, Samsul; Isjoni, Isjoni; Azhar, Azhar (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
The main objective of this research was reveal in detail by facts and data to get a complete image about the implementation of improvement program of educator quality at integrated elementary school Al-Fikri Islamic Green School Pekanbaru. This research specifically aimed reveal information objectively and empirically that relates understanding of improvement program of teachers’ quality, implementation of improvement program types, the supporting and abstracting factors in the implementation of the program and the effects of the implementation of the program and the effects of the implementation of the program at integrated elementary school Al-Fikri Islamic Green School Pekanbaru. This research used qualitative approach; the data were collected by interview, observation, and documentation. The data were analyses by descriptive qualitative with descriptive presentation, and triangulation was used know the data validity. The result showed that the teachers understand the improvement program of the teacher quantity well. The improvement programs of teachers’ quality at this school which were actualized in some programs such as education and training, ta’lim, kkg, teacher meeting, supervision, seminars workshop, study tour, character school programs could be done well. It was showed that there were supporting and obstructing factors on this program. Then, this program had positive effect toward the development of teacher competence optimally, positive effect an teacher service students, positive effect an teacher service to students’ parents, and positive effect an school quality.